Prospects of Frequency-Time Correlation Analysis for Detecting Pipeline Leaks by Acoustic Emission Method; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Faerman V. A. Vladimir Andreevich; Cheremnov A. G.; Avramchuk V. V.; Luneva E. E. Elena Evgenievna (Modern Technologies of Oil and Gas Pipelines and Storage Tanks. Process Simulation of Oil and Gas Transportation, 2014)
Title screen